2015
DOI: 10.1515/bjmg-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chromosomal Abnormalities in Infertile Couples in Romania

Abstract: The purpose of this study was to establish a correlation between the presence of chromosomal abnormalities in one of the partners and infertility. This retrospective study was performed at the Department of Reproductive Medicine, Life Memorial Hospital, Bucharest, Romania, between August 2007 to December 2011. Two thousand, one hundred and ninety-five patients with reproductive problems were investigated, and the frequency of chromosomal abnormalities was calculated. The control group consisting of 87 fertile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…In this study, as part of the routine evaluation of the infertile couple, karyotype allowed the identification of chromosome abnormalities in 233 couples, which accounts for 7.80% (233/2990) of our population. This is consistent with recent studies [11][12][13] that reported a similar prevalence of chromosomal anomalies in the infertile population, a rate 2-3 times higher than the general population [14].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, as part of the routine evaluation of the infertile couple, karyotype allowed the identification of chromosome abnormalities in 233 couples, which accounts for 7.80% (233/2990) of our population. This is consistent with recent studies [11][12][13] that reported a similar prevalence of chromosomal anomalies in the infertile population, a rate 2-3 times higher than the general population [14].…”
Section: Discussionsupporting
confidence: 93%
“…Mosaics were by far the most prevalent anomaly, accounting for 50.85% of affected individuals, and were mainly found in women, mosaic monosomy X being the most common. This represents an important cause of infertility, considering that primary amenorrhea and lack of pubertal development presents in 90% of women with 45,X or 45,X/46,XY, 45,X/46,XX or 45,X/ 47,XXX mosaicism [15], and is consistent with findings from similar studies [13]. Because it has been shown that the frequency of low-level X aneuploidy is correlated with age and gender but not with reproductive history [9], we conducted the same analysis performed in Table 4 for all couples but removing all the mosaic cases.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of chromosomal abnormalities in the general population is less than 1% [12]. Reciprocal translocation (RT) is one of the most frequent structural rearrangements observed in humans [13]. The individuals carrying this type of translocation are clinically normal, but they do have an increased risk of having children with unbalanced karyotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Translocations involving both the homologues of chromosome 13 and the homologues of chromosome 21 were observed in three women. Translocation between chromosomes(13,22) and(15,21) was identified in one woman and one man respectively.…”
mentioning
confidence: 99%
“…Among the chromosomal alterations, polymorphic variants are known to occur in 2.7% of the general population. However, much higher frequencies (12.2%–38%) have been reported in infertile males (Kate et al., ; Mierla, Malageanu, Tulin, & Albu, ). We found that polymorphic chromosomal variants were the most common ones (11.5%) in our present study, higher than in some Western countries (0.8%–3.2%) (Akbari et al., ; Frouzandeh et al., ; Mohammed et al., ; Rao et al., ) and lower than in the India region (16.7%) (Kate et al., ).…”
Section: Discussionmentioning
confidence: 95%